Amyrel, a novel glucose-forming α-amylase from Drosophila with 4-α-glucanotransferase activity by disproportionation and hydrolysis of maltooligosaccharides. (8th May 2021) - Feller, Georges; Bonneau, Magalie; Da Lage, Jean-Luc
Abstract: The α-amylase paralogue Amyrel present in true flies (Diptera Muscomorpha) has been classified as a glycoside hydrolase in CAZy family GH13 on the basis of its primary structure. Here, we report that, in fact, Amyrel is currently unique among animals as it possesses both the hydrolytic α-amylase activity (EC 3.2.1.1) and a 4-α-glucanotransferase (EC 2.4.1.25) transglycosylation activity. Amyrel reacts specifically on α-(1–4) glycosidic bonds of starch and related polymers but produces a complex mixture of maltooligosaccharides, which is in sharp contrast with canonical animal α-amylases. With model maltooligosaccharides G2 (maltose) to G7, the Amyrel reaction starts by a disproportionation leading to G n − 1 and G n +  1 products, which by themselves become substrates for new disproportionation cycles. As a result, all detectable odd- and even-numbered maltooligosaccharides, at least up to G12, were observed. However, hydrolysis of these products proceeds simultaneously, as shown by p -nitrophenyl-tagged oligosaccharides and microcalorimetry, and upon prolonged reaction, glucose is the major end-product followed by maltose. The main structural determinant of these atypical activities was found to be a Gly-His-Gly-Ala deletion in the so-called flexible loop bordering the active site. Indeed, engineering this deletion in porcine pancreatic and Drosophila melanogaster α-amylases results in reaction patterns similar to those of Amyrel. It is proposed that this deletion provides more freedom to the substrate for subsites occupancy and allows a less-constrained action pattern resulting in versatile activities at the active site.